A kind of plugging agent for drilling fluid and preparation method thereof
By preparing barium phosphate-silk fibroin hybrids, the problem of insufficient stability and coupling of existing drilling fluid plugging agents in oil-based drilling environments has been solved, and more efficient plugging performance and deformation resistance have been achieved.
Patent Information
- Application Number
- CN202411533335.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing drilling fluid leak plugging agent has poor stability in oil-based drilling environments and lacks coupling with the inorganic matter interface, resulting in limited leak plugging performance.
By preparing a hybrid agar that contains phosphoric acid oligospholic and syquetin protein, use triamines to slowly generate phosphate polycases to avoid precipitation, and through heating and static storage Mechanical strength and toughness-phosphate-silk protein hybrid.
Improve the stability and coupling of the leakage in the drilling environment, enhance the binding force with the crack or pore interface, improve the leakage performance, and make the cracks or pores after blocking Ability and toughness.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plugging leaks in oil drilling, and more specifically, relates to a plugging agent for drilling fluid and a preparation method thereof. Background Art
[0002] With the deepening of oil and gas exploration and the development of domestic oil fields entering the middle and late stages, the probability of malignant well leakage is getting higher and higher during the drilling of deep fractured formations and pressure-deficient formations, which has a great impact on the control of oil and gas exploration drilling construction and drilling fluid costs. The research on new plugging agents for drilling fluids with good plugging effects, especially bridging plugging agents, is particularly important. Bridging plugging mainly uses a variety of plugging materials to prepare plugging slurry in a certain proportion, and then plugs cracks and pore channels, and plugs the leaking layer through bridging, supporting, connecting, sealing, filling and other effects. At present, there are many kinds of conventional plugging materials, such as hydrophilic and oleophobic types, hydrophilic and oleophilic types, etc., and most of the plugging agents in the prior art are also improved for these types.
[0003] For example, CN112745812A discloses a plugging agent for drilling fluid and a preparation method thereof, specifically, by designing a microcapsule modifier to improve the polymer structure, thereby improving the plugging property of the plugging agent. Another example is CN114479779A discloses a plugging agent for drilling fluid and a preparation method thereof, specifically, by adding highly elastic modified asphalt particles to improve the viscoelasticity and strength of the plugging agent. In summary, most of the prior art improves its plugging property by improving the structure or performance of the polymer component in the plugging agent. However, the applicant found that there are still certain defects in improving the plugging agent for drilling fluid from the perspective of the polymer component, because in addition to organic matter in the environment of oil-based drilling, there are also a large number of inorganic minerals, especially the cracks and pores in the drilling environment are mostly formed by the fracture or dislocation of inorganic matter, and the existing plugging agent lacks coupling with the surrounding inorganic matter. Even if there are some inorganic components in the existing plugging agent, the structure of the plugging agent itself is unstable, resulting in limited plugging performance.
[0004] Therefore, it is necessary to prepare a drilling fluid plugging agent that has strong structural stability and strong interface coupling with cracks and pores in the drilling environment. Summary of the invention
[0005] Aiming at the problem that the drilling fluid plugging agent in the prior art has poor stability itself and poor coupling with the drilling environment, which leads to limited plugging performance of the plugging agent, the present invention provides a plugging agent for drilling fluid and a preparation method thereof.
[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a plugging agent for drilling fluid of the present invention comprises the following steps:
[0008] (1) dissolving barium chloride in an ethanol solvent to obtain an alcohol solution of barium chloride, and then adding triethylamine to the alcohol solution of barium chloride and stirring the mixture to obtain a mixed alcohol solution A of barium chloride and triethylamine;
[0009] (2) dissolving phosphoric acid in an ethanol solvent to obtain an alcohol solution B of phosphoric acid;
[0010] (3) adding the alcohol solution B dropwise into the mixed alcohol solution A and stirring the mixture for at least 6 hours, and then washing the precipitate after centrifugation of the reaction product to obtain barium phosphate oligomers;
[0011] In the above steps, barium ions and triethylamine are present in the mixed alcohol solution A. By adding the alcohol solution B of phosphoric acid dropwise into the mixed alcohol solution A, barium phosphate oligomers can be slowly generated under the action of triethylamine to avoid the formation of barium phosphate precipitation. The reaction is stirred for at least 6 hours so that the product barium phosphate oligomers are stably dispersed in the alcohol solution to prepare for the subsequent reaction.
[0012] (4) preparing a silk fibroin solution, and then mixing the barium phosphate oligomer and the silk fibroin solution to obtain a hybrid precursor solution;
[0013] In the above steps, the barium phosphate oligomer has a certain degree of dispersibility in the aqueous solution, and after mixing it with the silk fibroin, it can be preliminarily coupled in the solution to form a hybrid precursor.
[0014] (5) first heating the hybrid precursor solution to 40° C. to 60° C. and stirring the solution for at least 10 min, and then incubating the hybrid precursor solution at room temperature for at least 1.5 h to obtain a barium phosphate-silk fibroin hybrid solution;
[0015] In the above steps, the hybrid precursor solution is stirred and reacted at 40°C to 60°C for no less than 10 minutes, so that the barium phosphate oligomers are embedded in the heavy chain and light chain of the silk fibroin and are evenly dispersed, and then it is incubated at room temperature to allow the barium phosphate oligomers and the silk fibroin to adapt and self-assemble to a stable state, thereby obtaining a barium phosphate-silk fibroin hybrid with both the strong mechanical strength and toughness of barium phosphate and the appropriate water absorption and lipophilicity of silk fibroin. The barium phosphate oligomers as inorganic substances can be coupled with the inorganic environment after forming a hybrid, especially after combining with the inorganic interface of the drilling environment, it has strong wear resistance and bonding force, so that the plugging environment has strong anti-deformation ability and toughness.
[0016] (6) First, the matrix asphalt, fiber material, graphite material, dispersant and water are shear-mixed uniformly, and then the barium phosphate-silk fibroin hybrid solution, curing agent and 4,4-diaminodiphenylmethane are added and stirred uniformly to obtain a drilling fluid plugging agent.
[0017] Furthermore, in the step (1), 4-8 g of BaCl2·2H2O is added to 0.8-1 L of ethanol, and the mixture is stirred at room temperature for 5-30 minutes to obtain an alcohol solution of barium chloride, and then 80-110 mL of triethylamine is added to the alcohol solution of barium chloride at room temperature and stirred for 5-30 minutes to obtain a mixed alcohol solution A.
[0018] Furthermore, in the step (2), 1-5 mL of H3PO4 is dissolved in 30-60 mL of ethanol to prepare an alcohol solution B of phosphoric acid.
[0019] Furthermore, in the step (3), the alcohol solution B is added dropwise to the mixed alcohol solution A at a rate of 5 to 15 mL / min and stirred for reaction. After the dropwise addition is completed, the reaction is continued for 6 to 24 hours. The reaction product is then centrifuged in a centrifuge at a speed of 2000 to 5000 rpm for 3 to 10 minutes. The precipitate is collected and washed with ethanol for 3 to 6 times to remove residual triethylamine, and then washed with deionized water for 1 to 3 times to remove ethanol, thereby obtaining barium phosphate oligomers.
[0020] Under the above reaction conditions, the barium phosphate oligomer prepared by the present invention has a unique chain crystal structure, and the length of the prepared barium phosphate oligomer monomer is about 20-40 nm, the width is about 1-5 nm, and has strong toughness and mechanical strength.
[0021] Furthermore, in the step (4), the preparation of the silk fibroin solution comprises:
[0022] S1. Take 8-12g of silkworm cocoons, cut them into pieces, and place them in a 0.01-0.05mol / L Na2CO3 aqueous solution and boil them at a temperature not lower than 85°C for 20-60 minutes to remove sericin;
[0023] S2, after washing with deionized water for 3 to 5 times to remove residual sericin, the boiled silk was dried at room temperature;
[0024] S3, placing the dried silk in 50-60 mL 8-10 mol / L lithium bromide solution, dissolving the silk at 50-70°C for 3-8 hours to obtain a silk fibroin precursor solution;
[0025] S4, dialyzing the obtained silk fibroin precursor solution with deionized water using a 3500 Da cutoff dialysis membrane for 48 to 96 hours to remove lithium bromide;
[0026] S5. Centrifuge the dialyzed solution at 8000-12000 rpm for 15-30 minutes at 0-10°C to remove the precipitate to obtain a silk fibroin solution.
[0027] Furthermore, in the step (4), the barium phosphate oligomer and the silk fibroin solution are mixed at a mass ratio of barium phosphate:silk fibroin = 1:(3-10) to obtain a hybrid precursor solution, wherein the concentration of the barium phosphate oligomer is controlled at 5-30 mg / mL by adding deionized water.
[0028] Under the above-mentioned appropriate mass ratio, a chain space of silk fibroin compatible with the barium phosphate oligomer can be created, which facilitates the embedding of the barium phosphate oligomer into the silk fibroin for self-assembly.
[0029] Furthermore, in the step (6), the weight percentages of the components are: 80-100 parts of matrix asphalt, 4-18 parts of fiber material, 5-25 parts of graphite material, 20-30 parts of barium phosphate-silk fibroin hybrid, 1-10 parts of dispersant, 4-15 parts of curing agent, 0.5-3 parts of 4,4-diaminodiphenylmethane, and 130-180 parts of total water.
[0030] Furthermore, in the step (6), the matrix asphalt is one or more of straight-run asphalt, oxidized asphalt, solvent deasphalted asphalt, and natural asphalt, and its softening point is 35-80°C; the curing agent is one or more of hydrogenated tallow propanediamine, hexadecyl dimethyl tertiary amine, and octadecyl dimethyl tertiary amine; the dispersant is at least one or more of Tween-80, Tween-60, and Tween-40; the fiber material includes one or more of regenerated cellulose fiber, regenerated protein fiber, and regenerated starch fiber, and the length of the fiber material is 0.1-5.0 mm; the graphite material is at least one or more of flake graphite, elastic graphite, or expanded graphite.
[0031] Furthermore, in the step (6), when the barium phosphate-silk fibroin hybrid solution is added and stirred, barium phosphate powder or barium phosphate dispersion is added and stirred together; wherein the mass fraction of barium phosphate in the barium phosphate powder or barium phosphate dispersion is 0.8 to 6 parts, and the particle size thereof is 0.1 to 5 μm.
[0032] In the above steps, the added barium phosphate microparticles have a similar crystal structure to the barium phosphate oligomers. After being prepared into a plugging agent for drilling fluid, the barium phosphate microparticles can be coupled with the barium phosphate-silk fibroin hybrid. At the same time, the barium phosphate microparticles have strong wear resistance and mechanical strength, which can further enhance the bonding force between the plugging agent for drilling fluid and the crack or pore interface in the drilling environment, thereby improving the plugging performance.
[0033] The present invention also protects a plugging agent for drilling fluid, which is prepared by any one of the preparation methods described above.
[0034] 3. Beneficial effects
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) A method for preparing a plugging agent for drilling fluid of the present invention. The prepared plugging agent for drilling fluid can absorb water or oil appropriately in the cracks or pores in the drilling environment to expand and plug them. At the same time, since the barium phosphate-silk fibroin hybrid has strong mechanical strength, toughness, and coupling with the organic interface and inorganic interface in the drilling environment, the bonding force between the plugging agent and the interface of the cracks or pores in the drilling environment is enhanced, and the plugging performance of the plugging agent is improved, so that the cracks or pores in the drilling environment have strong pressure-bearing, anti-deformation and toughness after plugging.
[0037] (2) A plugging agent for drilling fluid of the present invention is obtained by the preparation method of the present invention and has all the beneficial effects of the preparation method of the present invention. DETAILED DESCRIPTION
[0038] The more detailed description of the embodiments of the present invention below is not intended to limit the scope of the claimed invention, but is merely for illustration and not to limit the description of the features and characteristics of the present invention, so as to propose the best mode for performing the present invention, and to be sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs; the terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0040] The preparation process of the silk fibroin solution in the present invention is as follows:
[0041] S1. Take 8-12g of silkworm cocoons, cut them into pieces, and place them in a 0.01-0.05mol / L Na2CO3 aqueous solution and boil them at a temperature not lower than 85°C for 20-60 minutes to remove sericin;
[0042] S2, after washing with deionized water for 3 to 5 times to remove residual sericin, the boiled silk was dried at room temperature;
[0043] S3, placing the dried silk in 50-60 mL 8-10 mol / L lithium bromide solution, dissolving the silk at 50-70°C for 3-8 hours to obtain a silk fibroin precursor solution;
[0044] S4, dialyzing the obtained silk fibroin precursor solution with deionized water using a 3500 Da cutoff dialysis membrane for 48 to 96 hours to remove lithium bromide;
[0045] S5. Centrifuge the dialyzed solution at 8000-12000 rpm for 15-30 minutes at 0-10°C to remove the precipitate to obtain a silk fibroin solution.
[0046] It should be noted that there are a variety of preparation methods for silk fibroin in the prior art. The present invention only provides a preparation method suitable for the plugging agent in this case. In addition, other preparation methods in the prior art can also be used, which will not be listed here.
[0047] The mass concentration of the final silk fibroin solution can be determined by the following method, which is only an example and not a limitation: the silk fibroin solution is divided into two solutions with a volume of V, one of which is dried or freeze-dried, and the mass of the remaining solid or gel is weighed, and the mass divided by V is the mass concentration of the silk fibroin. After the mass concentration is determined, it can be adjusted to the required specific concentration by adding water for dilution or concentration.
[0048] The present invention is further described below in conjunction with specific embodiments. Example 1
[0049] This embodiment provides a plugging agent for drilling fluid, and the preparation method thereof specifically comprises the following steps:
[0050] (1) 4.88 g of BaCl2·2H2O was added to 0.8 L of ethanol, and the mixture was stirred at room temperature for 20 minutes to obtain an alcohol solution of barium chloride. Then, 100 mL of triethylamine was added to the alcohol solution of barium chloride at room temperature and the mixture was stirred for 15 minutes to obtain a mixed alcohol solution A.
[0051] (2) Dissolve 1.25 mL of H3PO4 in 50 mL of ethanol to prepare alcohol solution B of phosphoric acid;
[0052] (3) adding the alcohol solution B dropwise to the mixed alcohol solution A at a rate of 10 mL / min and stirring for reaction. After the dropwise addition is completed, the reaction is continued for 12 hours. The reaction product is then centrifuged in a centrifuge at a speed of 3000 rpm for 10 min. The precipitate is collected and washed with ethanol for 3 times to remove residual triethylamine, and then washed with deionized water for 3 times to remove ethanol, thereby obtaining barium phosphate oligomers.
[0053] (4) preparing a silk fibroin solution, and then mixing the barium phosphate oligomer and the silk fibroin solution at a mass ratio of barium phosphate: silk fibroin = 1:5 to obtain a hybrid precursor solution, wherein the concentration of the barium phosphate oligomer is controlled at 20 mg / mL by adding deionized water, and the concentration of the silk fibroin is 100 mg / mL;
[0054] (5) first heating the hybrid precursor solution to 45° C. and stirring the solution for 15 min, and then incubating the hybrid precursor solution at room temperature for 3 h to obtain a barium phosphate-silk fibroin hybrid solution;
[0055] (6) First, 85 parts of natural asphalt with a softening point of 60°C, 15 parts of 3.5 mm regenerated protein fiber material, 20 parts of flake graphite material, 6 parts of Tween-80 and water were shear-mixed uniformly, and then 24 parts of barium phosphate-silk fibroin hybrid solution, 8 parts of hexadecyl dimethyl tertiary amine and 2.5 parts of 4,4-diaminodiphenylmethane were added and stirred to obtain a drilling fluid plugging agent, in which the total water content was controlled at 145 parts.
[0056] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this example were measured:
[0057] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1. Example 2
[0058] This embodiment provides a plugging agent for drilling fluid, and the preparation method thereof specifically comprises the following steps:
[0059] (1) 7.32 g of BaCl2·2H2O was added to 1 L of ethanol, and the mixture was stirred at room temperature for 15 minutes to obtain an alcohol solution of barium chloride. Then, 100 mL of triethylamine was added to the alcohol solution of barium chloride at room temperature and the mixture was stirred for 20 minutes to obtain a mixed alcohol solution A.
[0060] (2) Dissolve 3 mL of H3PO4 in 50 mL of ethanol to prepare alcohol solution B of phosphoric acid;
[0061] (3) adding the alcohol solution B dropwise to the mixed alcohol solution A at a rate of 7.5 mL / min and stirring to react. After the dropwise addition is completed, the reaction is continued for 18 hours. The reaction product is then centrifuged at 3000 rpm for 10 minutes in a centrifuge. The precipitate is collected and washed with ethanol for 3 times to remove residual triethylamine, and then washed with deionized water for 3 times to remove ethanol, thereby obtaining barium phosphate oligomers.
[0062] (4) preparing a silk fibroin solution, and then mixing the barium phosphate oligomer and the silk fibroin solution at a mass ratio of barium phosphate:silk fibroin = 1:6 to obtain a hybrid precursor solution, wherein the concentration of the barium phosphate oligomer is controlled at 20 mg / mL by adding deionized water, and the concentration of the silk fibroin is 120 mg / mL;
[0063] (5) first heating the hybrid precursor solution to 50° C. and stirring the solution for 20 min, and then incubating the hybrid precursor solution at room temperature for at least 4 h to obtain a barium phosphate-silk fibroin hybrid solution;
[0064] (6) First, 90 parts of natural asphalt with a softening point of 60°C, 12 parts of 3 mm regenerated protein fiber material, 16 parts of flake graphite material, 7 parts of Tween-80 and water were sheared and mixed evenly, and then 25 parts of barium phosphate-silk fibroin hybrid solution, 8 parts of octadecyl dimethyl tertiary amine and 3 parts of 4,4-diaminodiphenylmethane were added and stirred evenly to obtain a drilling fluid plugging agent, in which the total water content was controlled at 150 parts.
[0065] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this example were measured:
[0066] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1. Example 3
[0067] This embodiment provides a plugging agent for drilling fluid, and the preparation method thereof specifically comprises the following steps:
[0068] (1) 4.88 g of BaCl2·2H2O was added to 0.8 L of ethanol, and the mixture was stirred at room temperature for 20 minutes to obtain an alcohol solution of barium chloride. Then, 80 mL of triethylamine was added to the alcohol solution of barium chloride at room temperature and the mixture was stirred for 10 minutes to obtain a mixed alcohol solution A.
[0069] (2) Dissolve 1.5 mL of H3PO4 in 60 mL of ethanol to prepare alcohol solution B of phosphoric acid;
[0070] (3) adding the alcohol solution B dropwise to the mixed alcohol solution A at a rate of 5 mL / min and stirring for reaction. After the dropwise addition is completed, the reaction is continued for 24 hours. The reaction product is then centrifuged in a centrifuge at a speed of 4000 rpm for 8 minutes. The precipitate is collected and washed with ethanol for 3 times to remove residual triethylamine, and then washed with deionized water for 3 times to remove ethanol, thereby obtaining barium phosphate oligomers.
[0071] (4) preparing a silk fibroin solution, and then mixing the barium phosphate oligomer and the silk fibroin solution at a mass ratio of barium phosphate: silk fibroin = 1: 10 to obtain a hybrid precursor solution, wherein the concentration of the barium phosphate oligomer is controlled at 10 mg / mL by adding deionized water, and the concentration of the silk fibroin is 100 mg / mL;
[0072] (5) first heating the hybrid precursor solution to 60° C. and stirring the solution for 20 min, and then incubating the hybrid precursor solution at room temperature for 1.5 h to obtain a barium phosphate-silk fibroin hybrid solution;
[0073] (6) First, 100 parts of natural asphalt with a softening point of 60°C, 10 parts of 2 mm regenerated starch fiber material, 15 parts of expanded graphite material, 10 parts of Tween-60 and water are shear-mixed uniformly, and then 20 parts of barium phosphate-silk fibroin hybrid solution, 8 parts of hexadecyl dimethyl tertiary amine and 1.5 parts of 4,4-diaminodiphenylmethane are added and stirred to obtain a drilling fluid plugging agent, in which the total water content is controlled at 170 parts.
[0074] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this example were measured:
[0075] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1.
[0076] Comparative Example 1
[0077] The comparative example provides a conventional drilling fluid plugging agent, which is prepared by taking the following raw materials in the following weight proportion: 85 parts of natural asphalt with a softening point of 60°C, 15 parts of 3.5 mm regenerated protein fiber material, 20 parts of flake graphite material, 6 parts of Tween-80 and water are sheared and mixed evenly, and then 8 parts of hexadecyl dimethyl tertiary amine and 2.5 parts of 4,4-diaminodiphenylmethane are added and stirred evenly to obtain the drilling fluid plugging agent, wherein the total water content is controlled at 145 parts.
[0078] The ratio of the drilling fluid plugging agent in this comparative example 1 is basically the same as that in Example 1, and the main difference is that the barium phosphate-silk fibroin hybrid is removed.
[0079] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this comparative example were measured:
[0080] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1.
[0081] Comparative Example 2
[0082] The present comparative example provides a conventional drilling fluid plugging agent, which is prepared by taking the following raw materials in the following weight proportions: 85 parts of natural asphalt with a softening point of 60°C, 15 parts of 3.5 mm regenerated protein fiber material, 20 parts of flake graphite material, 6 parts of Tween-80 and water are sheared and mixed evenly, and then 8 parts of hexadecyl dimethyl tertiary amine, 4 parts of barium phosphate microparticles with a particle size of 3-4 μm, 16 parts of silk fibroin and 2.5 parts of 4,4-diaminodiphenylmethane are added and stirred evenly to obtain a drilling fluid plugging agent, wherein the total water content is controlled at 145 parts.
[0083] The ratio of the drilling fluid plugging agent in this comparative example 1 is basically the same as that in Example 1, the main difference is that 24 parts of barium phosphate-silk fibroin hybrid are replaced by 4 parts of barium phosphate microparticles with a particle size of 3-4 μm and 16 parts of silk fibroin.
[0084] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this comparative example were measured:
[0085] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1.
[0086] By comparing the examples and comparative examples 1 to 2, it can be seen that whether the barium phosphate-silk fibroin hybrid is removed or replaced with a single component of barium phosphate microparticles and silk fibroin, the final plugging performance is far inferior to the plugging agent of the embodiment. This is because the barium phosphate-silk fibroin hybrid in the plugging agent of the present invention has a unique structural stability, which can strengthen its own structural strength after swelling after absorbing liquid, and through the extrusion combination of silk fibroin, asphalt, etc. with the organic matter at the crack interface, and through the extrusion combination of the barium phosphate crystal chain with the inorganic matter at the interface, based on this multi-faceted effective combination, it is tightly coupled with the cracks or pores in the drilling environment, thereby improving the plugging performance.
[0087] Comparative Example 3
[0088] This comparative example provides a plugging agent for drilling fluid, and its preparation steps are basically the same as those in Example 1, with the main difference being that in step (3), the alcohol solution B is directly added to the mixed alcohol solution A and stirred for reaction for 12 hours.
[0089] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this comparative example were measured:
[0090] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1.
[0091] By comparison, it can be seen that the plugging performance of the plugging agent of Comparative Example 3 is significantly lower than that of Example 1, but it is still better than other comparative examples. This is because the reaction conditions of the barium phosphate oligomers are not well controlled in Comparative Example 3, resulting in a disordered crystal structure and agglomerates with larger particle sizes in the generated barium phosphate oligomers. These components are difficult to effectively embed into the silk protein chain for self-assembly, which leads to poor structural stability of the hybrid, so that the plugging performance of the plugging agent is poor. It can be seen that controlling the reaction conditions of step (3) is very necessary for the stable and orderly growth of barium phosphate oligomers. Example 4
[0092] This embodiment provides a plugging agent for drilling fluid, and its preparation steps are basically the same as those in Example 1, with the main difference being that in step (6), 4 parts of barium phosphate powder with a particle size of 3-4 μm are further added and stirred together to prepare the plugging agent.
[0093] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this example were measured:
[0094] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1. Example 5
[0095] This embodiment provides a plugging agent for drilling fluid, and its preparation steps are basically the same as those in Example 1, with the main difference being that in step (6), 1 portion of barium phosphate powder with a particle size of 3-4 μm is further added and stirred together to prepare the plugging agent.
[0096] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this example were measured:
[0097] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1. Example 6
[0098] This embodiment provides a plugging agent for drilling fluid, and its preparation steps are basically the same as those in Example 1, with the main difference being that in step (6), a dispersion containing 6 parts of barium phosphate microparticles with a particle size of 3-4 μm is further added and stirred together to prepare the plugging agent.
[0099] The pressure bearing capacity and dynamic water loss of the drilling fluid plugging agent prepared in this example were measured:
[0100] The plugging agent and base slurry were made into plugging slurry at a ratio of 1:4, wherein the base slurry was obtained by adding 1.25g of anhydrous sodium carbonate and 25g of bentonite to 500mL of water, stirring at room temperature for 30min, and then standing for one day. The plugging slurry was then squeezed into the plugging module with a 3mm crack, and after solidification, compressed gas was used to apply pressure to obtain the pressure bearing capacity data. In addition, the HPHT dynamic leakage meter was used to measure the plugging effect of the plugging agent. The test results are recorded in Table 1.
[0101] Table 1. Comparison of performance of plugging agents obtained in various implementation methods
[0102]
[0103] By comparing Examples 1 to 6, it can be seen that Examples 4 to 6 can further improve the plugging performance of the plugging agent by further adding barium phosphate microparticles, especially the pressure bearing capacity is significantly improved compared with Examples 1 to 3. This is largely due to the fact that the barium phosphate microparticles can be coupled with the barium phosphate-silk fibroin hybrid. At the same time, the barium phosphate microparticles have strong wear resistance and mechanical strength. After the plugging agent is plugged, the interfacial bonding force between the plugging agent and the crack can be further strengthened, thereby improving the plugging performance. By comparing Examples 4 to 6, it can be found that after the relative mass share of barium phosphate microparticles reaches 4 parts, its strengthening performance basically reaches the upper limit. This is probably because the excess barium phosphate microparticles are in a disordered dispersed state and cannot effectively strengthen the structural stability of the plugging slurry after curing.
[0104] The present invention has been described in detail above in conjunction with specific exemplary embodiments. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and any such modifications and variations, if any, will fall within the scope of the present invention described herein. In addition, the background art is intended to illustrate the current status and significance of the research and development of the present technology and is not intended to limit the present invention or the application field of the present application and the present invention.
[0105] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are recognizable by those skilled in the art based on the foregoing detailed description, such as combinations between the various embodiments, adaptive changes and / or replacements. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the attached claims and their legal equivalents, rather than by the description and examples given above.
[0106] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail. When flow, power, refractive index, time, or other values or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 is understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction.
Claims
1. A method for preparing a plugging agent for drilling fluid, characterized in that: The steps include: (1) dissolving 4-8 g of barium chloride in 0.8-1 L of ethanol solvent to obtain an alcohol solution of barium chloride, and then adding 80-110 mL of triethylamine to the alcohol solution of barium chloride and stirring to obtain a mixed alcohol solution A of barium chloride and triethylamine; (2) Dissolve 1-5 mL of phosphoric acid in 30-60 mL of ethanol solvent to obtain alcohol solution B of phosphoric acid; (3) adding the alcohol solution B dropwise into the mixed alcohol solution A and stirring the mixture for at least 6 hours, and then washing the precipitate after centrifugation of the reaction product to obtain barium phosphate oligomers; (4) preparing a silk fibroin solution, and then mixing the barium phosphate oligomer and the silk fibroin solution to obtain a hybrid precursor solution; (5) first heating the hybrid precursor solution to 40° C. to 60° C. and stirring the solution for at least 10 min, and then incubating the hybrid precursor solution at room temperature for at least 1.5 h to obtain a barium phosphate-silk fibroin hybrid solution; (6) Firstly, the matrix asphalt, the fiber material, the graphite material, the dispersant and the water are uniformly mixed by shearing, and then the barium phosphate-silk fibroin hybrid solution, the curing agent and the 4,4-diaminodiphenylmethane are added and stirred to obtain a drilling fluid plugging agent; wherein the curing agent is one or more of hydrogenated tallow propanediamine, hexadecyl dimethyl tertiary amine and octadecyl dimethyl tertiary amine; the dispersant is at least one or more of Tween-80, Tween-60 and Tween-40; the fiber The fiber material includes one or more of regenerated cellulose fiber, regenerated protein fiber, and regenerated starch fiber, and the length of the fiber material is 0.1-5.0 mm; the mass parts of each component are: 80-100 parts of matrix asphalt, 4-18 parts of fiber material, 5-25 parts of graphite material, 20-30 parts of barium phosphate-silk fibroin hybrid, 1-10 parts of dispersant, 4-15 parts of curing agent, 0.5-3 parts of 4,4-diaminodiphenylmethane, and the total content of water is 130-180 parts.
2. The method for preparing a plugging agent for drilling fluid according to claim 1, characterized in that: In the step (1), 4-8 g of BaCl2·2H2O is added to 0.8-1 L of ethanol, and the mixture is stirred at room temperature for 5-30 minutes to obtain an alcohol solution of barium chloride. Then, 80-110 mL of triethylamine is added to the alcohol solution of barium chloride at room temperature and stirred for 5-30 minutes to obtain a mixed alcohol solution A.
3. The method for preparing a plugging agent for drilling fluid according to claim 1, characterized in that: In the step (2), 1-5 mL of H3PO4 is dissolved in 30-60 mL of ethanol to prepare an alcohol solution B of phosphoric acid.
4. The method for preparing a plugging agent for drilling fluid according to claim 1, characterized in that: In the step (3), the alcohol solution B is added dropwise to the mixed alcohol solution A at a rate of 5 to 15 mL / min and stirred for reaction. After the dropwise addition is completed, the reaction is continued for 6 to 24 hours. The reaction product is then centrifuged in a centrifuge at a speed of 2000 to 5000 rpm for 3 to 10 minutes. The precipitate is collected and washed with ethanol for 3 to 6 times to remove residual triethylamine, and then washed with deionized water for 1 to 3 times to remove ethanol, thereby obtaining barium phosphate oligomers.
5. The method for preparing a plugging agent for drilling fluid according to claim 1, characterized in that: In the step (4), the preparation of the silk fibroin solution comprises: S1. Take 8-12g of silkworm cocoons, cut them into pieces, and place them in a 0.01-0.05mol / L Na2CO3 aqueous solution and boil them at a temperature not lower than 85°C for 20-60 minutes to remove sericin; S2, after washing with deionized water for 3 to 5 times to remove residual sericin, the boiled silk was dried at room temperature; S3, placing the dried silk in 50-60 mL 8-10 mol / L lithium bromide solution, dissolving the silk at 50-70°C for 3-8 hours to obtain a silk fibroin precursor solution; S4, dialyzing the obtained silk fibroin precursor solution with deionized water using a 3500 Da cutoff dialysis membrane for 48 to 96 hours to remove lithium bromide; S5. Centrifuge the dialyzed solution at 8000-12000 rpm for 15-30 minutes at 0-10°C to remove the precipitate to obtain a silk fibroin solution.
6. The method for preparing a plugging agent for drilling fluid according to claim 1, characterized in that: In the step (4), the barium phosphate oligomer and the silk fibroin solution are mixed at a mass ratio of barium phosphate:silk fibroin=1:(3-10) to obtain a hybrid precursor solution, wherein the concentration of the barium phosphate oligomer is controlled at 5-30 mg / mL by adding deionized water.
7. The method for preparing a plugging agent for drilling fluid according to claim 1, characterized in that: In step (6), the matrix asphalt is one or more of straight-run asphalt, oxidized asphalt, solvent deasphalted asphalt, and natural asphalt, and its softening point is 35-80°C; the graphite material is at least one or more of flake graphite, elastic graphite, or expanded graphite.
8. The method for preparing a plugging agent for drilling fluid according to any one of claims 1 to 7, characterized in that: In the step (6), when the barium phosphate-silk fibroin hybrid solution is added and stirred, barium phosphate powder or barium phosphate dispersion is added and stirred together; wherein the mass fraction of barium phosphate in the barium phosphate powder or barium phosphate dispersion is 0.8 to 6 parts, and the particle size thereof is 0.1 to 5 μm.
9. A plugging agent for drilling fluid, characterized in that: The method is prepared according to any one of claims 1 to 8.
Citation Information
Patent Citations
Plugging agent for drilling fluid and preparation method thereof
CN112745812A
Plugging agent for drilling fluid and preparation method thereof
CN114479779A
Method for production of barium phosphate by use of reaction extrusion technology
CN103950910A
Composite scaffold material and preparation method and application thereof
CN110064074A